Outcomes of EUS-guided choledochoduodenostomy as primary drainage for distal biliary obstruction with covered self-expandable metallic stents - Kuraoka, Naosuke; Hara, Kazuo; Okuno, Nozomi; Kuwahara, Takamichi; Mizuno, Nobumasa; Shimizu, Yasuhiro; Niwa, Yasumasa; Terai, Shuji (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasonography-guided choledochoduodenostomy (EUS-CDS) is an alternative therapy for percutaneous transhepatic biliary drainage. Outcomes of EUS-CDS for distal biliary tract obstruction with a covered self-expandable metallic stent (SEMS) as a primary drainage technique are unclear because there are few relevant reports. This study aimed to determine outcomes in patients undergoing EUS-CDS using SEMS as the primary drainage technique for malignant distal biliary duct obstruction.Patients and methods This retrospective study was conducted at Aichi Cancer Center Hospital, from January 2010 to July 2018, using data from our database.Results EUS-CDS was performed as a primary drainage technique for 92 patients. The technical success rate was 92.8 %, and the clinical success rate was 91.6 %. The overall incidence of adverse events was 15.7 %. The median stent patency time for the EUS-CDS was 396 days. Nineteen patients required re-intervention because of cholangitis or jaundice.Conclusion EUS-CDS as a primary drainage technique using SEMS has high technical and clinical success rates. It should be considered an effective drainage method with respect to long-term stent patency, low re-intervention rates, and absence of severe complications.